2019
DOI: 10.1186/s12935-019-1079-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nomograms for predicting cause-specific survival and overall survival of stage I–III colon cancer patients: a large population-based study

Abstract: BackgroundThe purpose of this study was to build functional nomograms based on significant clinicopathological features to predict cause-specific survival (CSS) and overall survival (OS) in patients with stage I–III colon cancer.MethodsData on patients diagnosed with stage I–III colon cancer between 2010 and 2015 were downloaded from the Surveillance, Epidemiology, and End Results (SEER) database. Univariate and multivariate Cox analyses were used to identify independent prognostic factors, which were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…Several studies have reported better performance of nomogram model than conventional staging systems and proposed it as a promising tool for prognosis evaluation [24][25][26]. The nomograms developed in our study also presented better prediction capacity than AJCC 7th staging system.…”
Section: Discussionsupporting
confidence: 50%
“…Several studies have reported better performance of nomogram model than conventional staging systems and proposed it as a promising tool for prognosis evaluation [24][25][26]. The nomograms developed in our study also presented better prediction capacity than AJCC 7th staging system.…”
Section: Discussionsupporting
confidence: 50%
“…In view of the WBC of patients with viral infection is usually not high[21,22], although it was unassociated in multivariate analysis, we still kept it in the process of establishing the diagnostic nomogram.Finally, the nomogram incorporates 4 items of the imaging features, epidemiological contact history and WBC count status. Nomogram is a visualization of regression analysis, which is more and more widely used in clinical disease diagnosis, prognosis evaluation and efficacy evaluation[23][24][25][26]. Our results show that the nomogram based on imaging features has good sensitivity and specificity in the diagnosis of COVID-19 pneumonia.…”
mentioning
confidence: 76%
“…Nomogram is a visualization of regression analysis, which is widely used in clinical disease diagnosis and prognosis evaluation [9][10][11][12]. In this study, we developed and validated a novel nomogram to predict the mortality risk among elderly patients with ARF.…”
Section: Discussionmentioning
confidence: 99%